A Bayesian approach to exploring expertise and putting success in adolescent and young adult golfers. (November 2021) - Carey, L.M.; Stone, J.A.; Hunter, A.M.; Donaldson, D.I.
Abstract: Objectives: Putting behaviour was examined to explore if age influenced performance and the development of motor and perceptual-cognitive expertise during late adolescence and early adulthood. We also examined if motor control and perceptual-cognitive expertise was related to performance on a representative putting task. Method: Twenty elite golfers (15 male; 17–24 years old; mean handicap of 0.5) completed eight straight and eight sloped putts at two distances (8ft/2.44m and 15ft/4.57m), on an indoor golf surface. Participants wore an eye tracker whilst putting and putting performance was assessed via putts holed and eye-movement behaviour, examining Quiet Eye (QE, the duration of the final fixation on the ball). A baseline profile for each participant was created using kinematic stroke data (collected using SAM PuttLab), average putts per round, greens in regulation and current practice hours (subjective self-report measures). Results: Bayesian statistical analysis revealed 'moderate' evidence that age and baseline kinematic factors did not influence putting success rates. Eye movement data revealed 'moderate' evidence that i) successful performance was associated with less variability in QE duration and ii) extended periods of QE were associated with a decline in performance. Previous experience and current skill level were ruled out as potential confounds. Conclusion: Our findings reveal that performance and perceptual-cognitive expertise, did not improve with age. We suggest that post 18 years, age should not be considered a factor in talent development programmes for golf putting. We discuss the benefits of adopting a Bayesian approach and suggest future studies employ longitudinal designs to examine changes in expertise over time. Highlights: Empirical evidence on age-related expertise in golf putting from late adolescence to young adulthood is missing. Bayesian analysis shows performance and perceptual-cognitive expertise does not increase with age during this key period. Irrespective of age, perceptual-cognitive expertise was linked to performance. To enable evidence-based talent selection we recommend tracking individual development during this key period.